4 - Sous-information et sous-développement en Afrique : éléments de recherche corrélationnelle - Loukou, Alain François (Africa Development, 2021)
A new problem of development in Africa is the question linked to the access to information and to the understanding of its importance. For lack of adequate ICTs equipments, access to information in Africa is not easy for many of its inhabitants. Moreover, for various reasons, the even importance of information in socioeconomic practices is not always fully appreciated in Africa. But, nowadays, as well in the South as in the North, human activities would struggle to function effectively without information resources in sufficient quantity. Thus, today, any country or continent which would suffer for long time from insufficient information provision might be prone to what we could possibly call, by analogy, hypoinformationosis which consequences are severe on its socioeconomic development process. Despite the crystallization of such a reality, technical and economical indicators show that Africa is very deficient in matter of information production and consumption. In this view, this article aims at contributing to the improvement of the understanding of information role in present human activities. To achieve this, we will use the analytical and operational approaches.